Fiscal Policy for the Crisis. (Policy Papers; Policy Paper ;, 2008)
The current crisis calls for two main sets of policy measures. First, measures to repair the financial system. Second, measures to increase demand and restore confidence. While some of these measures overlap, the focus of this note is on the second set of policies, and more specifically, given the limited room for monetary policy, on fiscal policy.